Efficacy of combined use of Tetradium ruticarpum (A. juss.) patch and Chinese massage (tuina) for the treatment of insomnia in elderly chronic heart failure patients - Lai Meili; Zhou Lidan; Liu Yingying; You Mengsu; Teng Xiaoqiong (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. The objective of the paper was to evaluate the efficacy of Tetradium ruticarpum (A. Juss.) patch (TRP) in combination with Chinese massage (tuina) for the treatment of insomnia in elderly patients with chronic heart failure (CHF). Methods. A cohort of 320 elderly CHF patients with comorbid insomnia, treated at the Zhejiang University of Traditional Chinese Medicine Affiliated Wenzhou Hospital from January 2019 to July 2022, were enrolled and equally divided into four groups (80 patients per group). The control group received standard pharmacological intervention with eszopiclone. Patients in the TRP group received TRP alone, while those in the tuina group received tuina therapy alone. Patients in the combined treatment group received both TRP and tuina therapy. All treatments lasted 14 days. Sleep quality was assessed at baseline and then on days 7 and 14 after treatment using the Pittsburgh Sleep Quality Index Scale (PSQI). Results. There were significant reductions in total PSQI scores in all groups on day 7 compared to baseline (p < 0.05). On day 14, the combined treatment, tuina, and TRP groups showed significantly reduced total PSQI scores relative to baseline, while a reversal of this trend was seen in the control group (p < 0.05). The combined treatment group had the lowest total PSQI scores on both days 7 and 14. Conclusion. The combined use of tuina and TRP may be effective in alleviating insomnia in elderly CHF patients. It resulted in consistent and sustained efficacy, potentially reducing the likelihood of drug resistance.